Moving beyond Idealistically Narrow Discourses in Citizenship Education. (March 2014) - Fischman, Gustavo E.; Haas, Eric
The main goal of this article is to provide conceptual guidelines to move the pedagogical debate in the field of citizenship education beyond idealistically narrow models. We begin by providing an overview of key shortcomings presented in most citizenship education programs, specifically in the United States of America. The second section presents the conceptual perspective of embodied cognition to discuss the prevalent metaphors and prototypes related to the notion of 'the nation as a family' commonly used in understanding citizenship education. The third and final section concludes with a set of suggestions for reconceptualizing the field of citizenship education using the tools of embodied cognition.